INST Institutional Ownership and Firm Value: A Study on the Bist Manufacturing Index - Doğan, Mesut (Ekonomika, 2020)
The aim of this research is to test the relation between institutional ownership and firm value. To accomplish this aim, data from 104 firms listed in the BIST (i.e. Borsa Istanbul) industrial index between 2006 and 2018 have been used. Studies on the structure of ownership have problems with endogeneity. In order to avoid these problems, this study adopted Durbin-Wu-Hausman test with advanced econometric techniques, Ordinary Least Squares (i.e. OLS), and Two-Stage Least Squares (i.e. 2SLS). As a result of the simultaneous equation system improved in this study, a positive relation between institutional ownership as an endogenous variable, and firm value has been located. Besides, it has been found that institutional investors are more interested in the firms that have a higher market performance.
Keywords: institutional ownership; firm value; endogeneity